EDUCATIONAL STRATEGY FOCUSING IN CHILDREN'S FEEDING'S HABIT:REGIONAL FOOD - Mariana Cavalcante Martins; Lorena Barbosa Ximenes; Cíntia Freitas Casimiro; Vanessa Gomes Silveira; Mirna Albuquerque Frota (Universidade Federal do Paraná, 2009)
The research aimed to develop educational strategies on diet during the complementary feeding and use ofregional food. Exploratory qualitative study developed in a Family Health Program in Maranguape - Ceará - Brasil. Datawere collected through a semi-structured interview with 13 mothers of children aged less than six months that wereenrolled to receive complementary feeding. The results were analyzed through Bardin's thematic analysis, and the emergedcategories were: biological needs of the child, Feeding; and Innovating feeding with regional food. Therefore, promotinghealth of children in supplementary feeding through the use of regional food is a subject that should be disseminated,especially in the group of families that suffer with inequality in terms of social injustice